WARUNG KOPI, MEDIA DAN KONSTRUKSI RUANG PUBLIK DI MAKASSAR - Faisal, Andi; Putra, Heddy Shri Ahimsa; Nugraha, Wisma Ch. R. (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2017)
In the last 15 years, especially in Makassar, there was a tendency for private and public activities at coffee shops. This study aims to reveal the practices and power relations that shape the reality of the public space of coffee shops in Makassar, both as public space and as a public sphere by using ethnographic methods and cultural studies analysis approach. The primary data collection was carried out through participant observation and in-depth interviews, while secondary data through note-taking techniques and photo documentation. The results showed that mass media had a significant role in shaping the reality of coffee shops. Strategic coalitions between coffee shop owners, radio stations (such as Mercurius FM and Fajar FM) and coffee connoisseurs have an impact on the commodification of public spaces in coffee shops. Print media such as Fajar and Tribun Timur also contribute in constructing reality with its own framing to obtain "news value that sells". Therefore, coffee shops in Makassar are not merely becoming spaces of (social) politics, but are also politicized through the politics of space for the benefit of each party.